2019
DOI: 10.21608/ejchem.2019.12976.1810
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and application of new reactive disperse dyes based on isatin derivatives and their Antibacterial activity

Abstract: A NEW two reactive disperse dyes based on a hybrid structure of isatin and benzanthrone or anthraquinone via 1, 3, 5 triazine spacer were prepared. The prepared compounds were characterized by 1 H-NMR, mass spectrometry and elemental analysis. The UV/vis absorption spectra and emission spectra were measured in N, N-dimethylformamide (DMF) solution at room temperature, the effects of substituent's on the emission spectra of these compounds were interpreted. The dyeing application of the prepared dyes on wool an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 23 publications
0
5
0
1
Order By: Relevance
“…It was found that the hetero dienophile must be prepared firstly although the reaction between 2,5-dihydrazino -1,3,4-thiadiazole and substituted benzaldehyde in acidic media in ratio (1:2) under reflux condition for (2 hrs) , whereas the hetero diene prepared at room temperature with stirring between hydrazine hydrate and substituted benzaldehyde in ratio (1:2) these two starting materials hetero diene and dienophile were undergoes Diels-Alder reaction via grinding and MWI technique as summarized in the following Scheme: Firstly, Schiff bases prepared through condensation reaction in acidic media. The structure of Schiff bases (3)(4)(5)(6) were established on the bases of their spectroscopic data, they show in FT-IR spectroscopy stretching vibration bands at (1653-1618 cm -1 ) due to the C=N functional group and stretching vibration band at (3316-3050 cm -1 ) due to the only NH functional group . Actually these Schiff bases were underwent Diels-Alder reaction with hetero dienes (7,8) under grinding for (30min) and then free-Solvent MWI with power (720 watt) at specific time to offered the hetero adducts (9-20) through one step intercyclization reaction , as shown in Scheme (1).…”
Section: -Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that the hetero dienophile must be prepared firstly although the reaction between 2,5-dihydrazino -1,3,4-thiadiazole and substituted benzaldehyde in acidic media in ratio (1:2) under reflux condition for (2 hrs) , whereas the hetero diene prepared at room temperature with stirring between hydrazine hydrate and substituted benzaldehyde in ratio (1:2) these two starting materials hetero diene and dienophile were undergoes Diels-Alder reaction via grinding and MWI technique as summarized in the following Scheme: Firstly, Schiff bases prepared through condensation reaction in acidic media. The structure of Schiff bases (3)(4)(5)(6) were established on the bases of their spectroscopic data, they show in FT-IR spectroscopy stretching vibration bands at (1653-1618 cm -1 ) due to the C=N functional group and stretching vibration band at (3316-3050 cm -1 ) due to the only NH functional group . Actually these Schiff bases were underwent Diels-Alder reaction with hetero dienes (7,8) under grinding for (30min) and then free-Solvent MWI with power (720 watt) at specific time to offered the hetero adducts (9-20) through one step intercyclization reaction , as shown in Scheme (1).…”
Section: -Results and Discussionmentioning
confidence: 99%
“…Synthesis of (9-20): (Lenardao, Lara et al 2007)Equimolare of compounds (3)(4)(5)(6) and dibenzylidine hydrazine(7&8) were grinding for (30min) followed by irradiation in a microwave oven for suitable time at (720 watt). Cooling then cold water was added to the reaction mixture, and the solid product was then filtered off and recrystallized from ethanol.…”
Section: Synthesis Of Diarylidine Hydrazines (7and8): (Sharma and Cho...mentioning
confidence: 99%
“…[1][2][3][4] Anti-tubercular and anti-inflammatory activities of heterocyclic hybrids with isatin (indole-2,3-dione) are being studied extensively. 5,6 The Mannich bases of isatin shows potent anti-tubercular activities in previous studies. 7,8 Anti-tubercular and anti-inflammatory properties of isatin and thiophene derivatives have been reported in the literature.…”
Section: Introductionmentioning
confidence: 93%
“…However, the large water consumption makes this process particularly not attractive on ecological grounds. In order to achieve effective production process, the fabric requires separately pretreatment bath to fabric has satisfactory levels of wetability, swelling and reduction of fibrillation tendency, which in turn, lead to a better dye uptake and increase the forces of dye-fiber interactions [11][12][13][14][15][16]. Moreover, several attempts have been made to sho exhaust two-bath processes of pretreatment and dyeing viscose into one-bath process.…”
Section: Introductionmentioning
confidence: 99%